The Effect of Compensation, Mutation and Work Discipline on the Performance of PT. Indomarco Prismatama Gunung Sahari Branch 2 North Jakarta - Richo Santuryan L; Subur Karyatun; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of compensation, mutation and work discipline on the performance of employees of PT. Indomarco Prismatama Gunung Sahari 2 Branch, North Jakarta. This type of research uses descriptive quantitative methods and inferential analysis using primary data in the form of a closed questionnaire to 100 respondents, and the data is analyzed using multiple linear regression analysis. From the data that has fulfilled the validity test, reliability test, classic assumption test and model feasibility test, the regression equation is obtained, as follows: Y = 0.171K + 0.277M + 0.533 DK The results of the regression analysis in this study show that compensation (X1) has a positive and significant effect on employee performance (Y), mutations (X2) have a positive and significant effect on employee performance (Y), work discipline (X3) has a positive and significant effect on employee performance (Y), In an effort to improve employee performance, PT. Indomarco Prismatama Branch Gunung Sahari 2 North Jakarta needs to pay attention and know what is the problem because it can be used as a basis for correcting weaknesses and maintaining effectiveness through compensation, transfers and good work discipline.